A screening UHPLC–MS/MS method for the analysis of amyloid peptides in cerebrospinal fluid of preclinical species. (January 2011) - Dillen, Lieve; Cools, Willy; Vereyken, Liesbeth; Timmerman, Philip
Background: Amyloid peptides are established biomarkers for Alzheimer's disease but their analysis presents major challenges.Results: In this article, we describe the use of ultra high-performance LC and API4000 triple quadrupole instrumentation for the quantification of amyloid peptides (Aβ1-38 and Aβ1-42 ) in cerebrospinal fluid (CSF), using electrospray ionization with negative ion multiple reaction monitoring transitions. Sample preparation was simplified by the addition of acetonitrile and ammonium hydroxide. Although excellent sensitivity and precision was demonstrated, we observed differences in matrix suppression effects when using artificial CSF versus canine CSF for calibration curves and quality control samples.Conclusion: A case study shows that the method can be used to determine the relative levels of two key peptides (Aβ1-38 and Aβ1-42 ) compared with their predose values (a screening assay) in support of preclinical studies.